Coaches` opinions about teaching defensive skills for youth handball teams - da Silva Musa, V.; Menezes, R. P. (International Journal of Sports Science & Coaching, 2022)
Purpose It can be observed that coaching in youth sports may be based on technique development, while it is inspired by high-performance sports. As it is observed a lack of research that addressed the coaching process with youth handball teams in the Brazilian context, this study aimed to analyze what is expected for the defensive phase and how it is taught.